Microalbuminuria como indicador presuntivo de daño renal en pacientes del Club de Diabéticos del Hospital IESS de Loja durante el período febrero-marzo 2014 - Guamán Chamba, Ángel Patricio (2014)
Diabetes mellitus is a metabolic disease it characterized by the inability to make enough insulin to the body, the same is chronic and destructive affecting all organs especially: heart, brain circulation, kidneys, retina; to prevent these complications have been used as microalbuminuria tests that allow early diagnosis of kidney damage (1). In the actuality Diabetes mellitus is the main cause of lower limb amputation and kidney it cause of blindness in the active economic population (2). In Ecuador this disease is among the 10 most frequent causes of death, in Loja, it is estimated that 5% of the population suffers diabetes.(3) For this reason this research was investigated was entitled MICROALBUMINURIA AS INDICATOR OF RENAL DAMAGE IN DIABETIC PATIENTS CLUB OF HOSPITAL IESS DE LOJA DURING FEBRUARY-MARCH 2014", the objectives were determined the microalbuminuria relation to age, gender and duration of illness, through a descriptive and cross-sectional quantitative study based on a total sample of 89 diabetic patients, to obtain the following conclusions that the 43.82% had elevated levels of microalbuminuria were determined by the immunochromatographic method, about of age 11.24% were between 75-84 years, and 10.11%, between 65-74 years, when analyzing gender was observed that 22.47% were female, and 21.35% of male gender, in the time of illness are among the 6-10 years with a 13.48% and from 11 to 20 years with 12.36%. KEYWORDS: diabetes, kidney damage, age, gender, microalbuminuria.